The European para sport coaching workforce: A quasi-professional space - Huntley, T. D.; Townsend, R. C.; Cronin, C.; Williams, C.; Hardwick, A.; Ryrie, A.; Lewis, C.; Mcquilliam, S.; Cushion, C.; Whitehead, A. (International Sport Coaching Journal, 2026)
Coaches in Paralympic and disability sport (Para coaching) play a significant societal role by providing opportunities for disabled people in sport and physical activity. Such is its importance; this role is now recognised by the European Union and its professionalisation agenda. Therefore, drawing on Abbott`s theory of professions and Thomas` social relational model of disability, this original transnational study considers critically the characteristics of the European Para coaching workforce. Data collection followed a mixed methodology via an online survey of Para coaches ( N = 275). Combining quantitative and qualitative data, the analysis generated three higher order themes, "Exclusion, differentiated labour force and working contexts," "Uneven coach education and development opportunities" and "Impairment effect as a source of coaches professional knowledge." These themes illuminate Para coaching as a quasi-professional space shaped by specific workforce characteristics and those mediated by sporting domains. The findings and recommendations prompt significant considerations for policy makers, coach educators, and sport organisations.